Semiotic Analysis of Artistic Expression and Social Criticism by Mural Masjo - Ratna Tri Maharani; Pujiyanto Pujiyanto; Robby Hidajat (Green Publisher Indonesia, 2024)
Murals are often a medium for conveying people's aspirations. However, most people think that murals are just graffiti on the wall with no meaning. In this case, mural artists play a role in voicing aspirations, criticism, ideas and things that are bothering society. Because murals do not only focus on the beauty of the mural artwork, but also have meaning and messages. Masjo, as a mural artist, sees phenomena around him that he uses as topics for murals. As happened some time ago, the Covid-19 pandemic has had a real impact on society. Masjo sees this phenomenon as sad. This research uses a qualitative descriptive method, using iconography and iconology semiotics to obtain markers of meaning contained in mural images. So that this research can explain or describe Masjo's mural work in detail. The results of this research are the meaning of artistic expression and messages of social criticism in Masjo's mural entitled 'Just stay at home'. The meaning of artistic expression in mural works tells how to survive in the Covid-19 pandemic situation. The social criticism in the mural discusses the role of the government which only advises people to stay at home, while the government does not provide guarantees for people's lives